Coping styles and mental health in response to societal changes during the COVID-19 pandemic. (August 2021) - Gurvich, Caroline; Thomas, Natalie; Thomas, Elizabeth HX; Hudaib, Abdul-Rahman; Sood, Lomash; Fabiatos, Kali; Sutton, Keith; Isaacs, Anton; Arunogiri, Shalini; Sharp, Gemma; Kulkarni, Jayashri
Background: Psychosocial responses to infectious disease outbreaks have the potential to inflict acute and longstanding mental health consequences. Early research across the globe has found wide ranging psychological responses to the current COVID-19 pandemic. Understanding how different coping styles can be effective in mitigating mental ill health would enable better tailored psychological support. Aims: The aim of this study was to gain an understanding of psychosocial responses to the COVID-19 pandemic, including depression, anxiety and distress, as well as effective coping styles in an Australian sample. Method: A sample of 1, 495 adults, residing in Australia between April 3rd and May 3rd 2020, completed an online survey which measured psychological distress (Impact of Events Scale-Revised), depression, anxiety, stress (DASS-21), as well as coping strategies (Brief COPE). Results: 47% of the respondents were experiencing some degree of psychological distress. Females experienced higher levels of depression, anxiety and stress than males. Coping strategies associated with better mental health were positive reframing, acceptance and humour. Conversely, self-blame, venting, behavioural disengagement and self-distraction were associated with poorer mental health. Conclusion: Rates of psychological symptoms amongst the Australian population are similar to those reported in other countries. Findings add to the growing literature demonstrating a gender disparity in the mental health impacts of COVID-19. Positive emotion focused coping strategies may be effective for reducing psychological symptoms. Understanding psychosocial responses including beneficial coping strategies are crucial to manage the current COVID-19 situation optimally, as well as to develop mental health response plans for future pandemics.